Novel strategies for Alzheimer's disease treatment: An overview of anti-amyloid beta monoclonal antibodies - Rygiel, Katarzyna (Indian J Pharmacol, 2016)
Alzheimer's disease (AD) is a multifactorial, progressive neurodegenerative disorder with a poor prognosis, and thus, novel therapies for AD are certainly needed in a growing population of elderly patients or asymptomatic individuals, who are at risk for AD, worldwide. It has been established that some AD biomarkers such as amyloid-beta load in the brain, precede the onset of the disease, by approximately 20 years. Therefore, the therapy to prevent or effectively treat AD has to be initiated before the emergence of symptoms. A goal of this review is to present the results of recent clinical trials on monoclonal antibodies against amyloid beta, used for the treatment of AD and also to address some of the current challenges and emerging strategies to prevent AD. In recent trials, a monoclonal antibody, i.e. solanezumab has shown some beneficial cognitive effects among mild AD patients. Ongoing studies with gantenerumab and crenezumab will examine when exactly the AD treatment, aimed at modifying the disease course has to be started. This review was based on Medline database search for trials on passive anti-AD immunotherapy, for which the main timeframe was set from 2012 to 2015.